Flexibilidad psicológica y burnout en trabajadores de salud: revisión aplicada - Cerpa Salazar, Paula Rosa (2023)
Healthcare workers represent an especially vulnerable population to burnout (BO) syndrome, for which it is necessary to study potentially protective personal resources such as psychological flexibility (PF). The purpose of this review is to identify the relationship between PF and BO symptoms in healthcare personnel, as well as to examine the measurement instruments used in the analyzed literature. A search process was conducted in the Scopus and Web of Science databases, according to the PRISMA guide (Page et al., 2021). As a result, 10 articles that related FP and BO, and met the eligibility criteria, were selected. In most studies, a significant negative correlation is reported between FP and BO. Likewise, it is estimated that PF is a significant negative predictor of BO. According to these findings, the higher the PF level, the fewer BO symptoms are experienced. The benefit of implementing interventions aimed at developing FP skills in this population is suggested. Likewise, the importance of standardizing the use of concepts associated with PF, as well as opting for PF measures with a more solid discriminant validity, is discussed.